2006
DOI: 10.1523/jneurosci.4310-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Bombardment Modulates Muscarinic Effects in Forelimb Motor Cortex

Abstract: Neocortical neurons in vivo exist in an environment of continuous synaptic bombardment, receiving a complex barrage of excitatory and inhibitory inputs. This background activity (by depolarizing neurons, increasing membrane conductance, and introducing fluctuations) strongly alters many aspects of neuronal responsiveness. In this study, we asked how it shapes neuromodulation of postsynaptic responses. Specifically, we examined muscarinic modulation of forelimb motor cortex, a brain area in which cholinergic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 60 publications
2
28
1
Order By: Relevance
“…The ACH-induced persistent hyperpolarization described here is in marked contrast to the ACH-induced persistent depolarization previously demonstrated in identified neocortical PCs (9)(10)(11)(12). Therefore, it is likely that this type of response is a unique feature of L4-SNs.…”
Section: Resultscontrasting
confidence: 90%
See 2 more Smart Citations
“…The ACH-induced persistent hyperpolarization described here is in marked contrast to the ACH-induced persistent depolarization previously demonstrated in identified neocortical PCs (9)(10)(11)(12). Therefore, it is likely that this type of response is a unique feature of L4-SNs.…”
Section: Resultscontrasting
confidence: 90%
“…In previous studies in rodents, a persistent hyperpolarization in response to ACH has only been observed in a few subpopulations of inhibitory neurons of the hippocampus and neocortex (30)(31)(32) as well as in extracortical regions of the CNS or in the PNS (33)(34)(35). In the neocortex, application of ACH has been reported to invariably induce a persistent depolarization in identified excitatory neurons (9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus it is probable that synapses that are globally modified by tDCS in the present study are more susceptible to cholinergic suppression of synaptic transmission during plasticity induction. A similar effect is also demonstrated by a recent study using a dynamic clamp system to mimic in-vivo-like background activities in motor cortical slices, in which cholinergic facilitation of LTP was attenuated in the presence of random background noise (Desai and Walcott, 2006).…”
Section: Ach Diminishes Tdcs-driven Neuroplasticitysupporting
confidence: 77%
“…Brain slices were prepared and electrophysiological recordings made essentially as previously described (Desai and Walcott, 2006;. Briefly, coronal sections of 350 m thickness containing medial prefrontal cortex were cut on a vibratome in ice-cold artificial CSF (ACSF) containing the following (in mM): 126 NaCl, 3 KCl, 1 NaH 2 PO 4 , 25 NaHCO 3 , 2 MgCl 2 , 2 CaCl 2 , and 25 dextrose.…”
Section: Methodsmentioning
confidence: 99%